Digital Campaign Melalui Akun Instagram @orbitfutureacademy.id Dalam Membangun Brand Awareness Orbit Future Academy - Niigata, Dinda Ramadhanty; Kurniasari, Ni Gusti Ayu Ketut (UHN IGB Sugriwa Denpasar, 2024)
In using current technology, especially in developing social media content that can create the characteristics or branding of a company. Orbit Future Academy is a training program that is different and also very flexible for training workers. Orbit Future Academy is carrying out a digital campaign which aims to convey information related to Artificial Intelligence which is a program from Orbit Future Academy via its official Instagram @orbitfutureacademyid as Instagram management. This research uses a qualitative descriptive method with research techniques focused on Focus Group Discussion (FGD). The FGD was carried out involving Orbit Future Academy employees. This research produces five things, namely research as original content management data, maximizing content design, media monitoring, building brand awareness by maximizing Instagram features and providing rewards for @orbitfutureacademy followers. These five things are important components in digital campaigns via Instagram accounts. @orbitfutureacademyid in building artificial intelligence brand awareness.